Pelaksanaan Hidden Curriculum dalam Pembentukan Nilai-nilai Toleransi pada Mata Pelajaran Pendidikan Kewarganegaraan (di SMKN 1 Kota Serang) - Rohmah, Siti; Dewi, Ratna Sari; Raharja, Reza Mauldy (CV. Rayyan Dwi Bharata, 2025)
Indonesia is one of the diverse countries with diverse religions, cultures, tribes, races, languages, and races. In this modern era, the paradigm of globalization greatly influences human nature and characteristics. Tolerance is actually not just accepting differences, but respecting each other. Tolerance is a basic element needed to realize an attitude of mutual understanding, respecting existing differences and becoming an entry point for creating conditions of harmony and dialogue between religious communities in community life. Various educational institutions accept students from various backgrounds, so this requires schools to instill the values of tolerance in all students, so that the learning process can run well. However, in reality, these things tend not to be the main focus of education in the current information era, because the ability to respect each other and recognize the diversity of students is very minimal. So, the need for a hidden curriculum in this problem. Although the existence of a hidden curriculum is not realized by students, this unplanned learning experience can still emerge, not only through interactions between students and teachers, but also through the relationship between students and their surroundings so that the values of tolerance are formed. This study aims to determine how the implementation of the hidden curriculum at SMKN 1 Kota Serang and what form the hidden curriculum takes at SMKN 1 Kota Serang and the supporting and inhibiting factors for the implementation of the hidden curriculum in the formation of tolerance values at SMKN 1 Kota Serang. This study uses a qualitative research type using observation, interview, and documentation methods. From the results of the study, it can be concluded that the implementation of the hidden curriculum running at SMKN 1 Kota Serang has been carried out well, based on the specific findings that the researcher found, the implementation of this hidden curriculum basically requires cooperation from various parties, both from the school and the parents of students. The form of activity is in the form of a hidden curriculum through habits (positive habits in class, habits that exist at school), hidden curriculum through class management, hidden curriculum through role models and relationships between teachers, hidden curriculum through school regulations, hidden curriculum through facilities and extracurricular activities. All forms of hidden curriculum activities certainly lead to learning in PKn and refer to the school curriculum, in addition to school habits that help to shape character, especially in tolerance values.